Airline Safety: Some Empirical Findings - Barnett, Arnold; Abraham, Michael; Schimmel, Victor (Management Science, 1979)
We consider the fatal accident records of 58 major world airlines, and in particular try to compare appropriately the safety records of airlines whose route structures overlap and which thus compete for passengers. We separately review data about the 18 principal U.S. domestic airlines and 40 major international flag carriers. A good part of effort involves trying to develop sensible measures of safety performance, and considering differences between airlines that might make misleading the direct comparison of their accident rates. Our analysis leads us to conclude that: As a group, the U.S. domestic carriers have achieved a safety record that is excellent in both absolute and relative terms. There is no real basis for identifying any of them as especially safe or especially dangerous, for the disparities in their observed accident records are smaller than would be expected from chance fluctuations alone. Among international airlines, however, divergences in safety records arise that are both substantial and statistically significant. Generally speaking, large airlines from “Westernized” countries seem demonstrably safer than those from most countries in Latin America, Eastern Europe, and the Middle East. In all segments of the airline industry, fatality rates have dropped over 50% in the last 15 years.